First person - Marie Rodinova (The Company of Biologists, 2019)
First Person is a series of interviews with the first authors of a selection of papers published in Disease Models & Mechanisms, helping early-career researchers promote themselves alongside their papers. Marie Vanisova (née Rodinova) is first author on 'Skeletal muscle in an early manifest transgenic minipig model of Huntington's disease revealed deterioration of mitochondrial bioenergetics and ultrastructure impairment', published in DMM. Marie is a PhD student in the lab of Hana Hansikova in the Department of Paediatrics and Adolescent Medicine, Charles University and General University Hospital in Prague, Czech Republic, investigating mitochondrial dysfunction in Huntington's disease (HD) and its role in the progress of HD.